Experimental study on the seismic behavior of prefabricated L-shaped concrete-filled steel tube with rectangular multi-cell columns under different lateral loading directions. (February 2021) - Chen, Huirong; Wang, Lai; Chen, Haitao; Cui, Wenbin
Abstract: Prefabricated residential buildings are becoming the focus of the construction industry. Simultaneously, in order to improve the seismic behavior of traditional RC special-shaped columns, a prefabricated special-shaped concrete-filled steel tube with rectangular multi-cell (S-CFST-R) column was proposed for residential systems. The seismic test of prefabricated L-shaped concrete-filled steel tube with rectangular multi-cell (L-CFST-R) columns was conducted in this study. Three full-scale L-shaped specimens with high practical guidance were designed which were based on the common parameters of residential buildings. A quasi-static test method under a low cycle load was used to simulate the earthquake action. Taking different loading directions (0°, + 45°, and + 135°) as the main research factors, the failure state, bearing capacity, hysteretic behavior, ductility, energy dissipation capacity, strength degradation, stiffness degradation, and strain change of each specimen were studied and analyzed. Moreover, a finite element model was developed to simulate L-CFST-R columns at different loading directions, and the simulation results agreed well with the experimental results. The influence of more loading directions on the ultimate bearing capacity and skeleton curve is analyzed comprehensively. The results indicated that multi-cell special-shaped steel tubes had a strong restraining effect on the core concrete, so the L-CFST-R columns under different lateral loading directions exhibited favorable seismic behavior, which is suitable for prefabricated residential buildings. Graphical abstract: Experimental study on the seismic behavior of prefabricated L-CFST-R columns under different lateral loading directions are presented. Three full-scale L-shaped specimens with high practical guidance were designed which were based on the common parameters of residential systems. Taking different loading directions (0°, +45°, and + 135°) as the main research factors, the failure behavior, bearing capacity, hysteretic behavior and other mechanical properties of the specimens were studied and analyzed. Unlabelled Image Highlights: A prefabricated special-shaped concrete-filled steel tube with rectangular multi-cell (S-CFST-R) column is proposed for residential systems The hysteretic curves, skeleton curves, ductility and other parameters obtained from the seismic test all reflect the favorable seismic behavior of L-CFST-R columns. Rectangular multi-cell steel tubes have a valid constraint effect on the core concrete by the analysis of strain. Reasonable FEM is established to analyze the influence of loading direction on L-CFST-R columns comprehensively.